Processing of multi-digit additions in high math-anxious individuals: psychophysiological evidence - NÚÑEZ-PEÑA, MARIA ISABEL; SUÁREZ-PELLICIONI, MACARENA (Frontiers in Psychology, 2015)
We investigated the time course of neural processing of multi-digit additions in high- (HMA) and low-math anxious (LMA) individuals. Seventeen HMA and 17 LMA individuals were presented with two-digit additions and were asked to perform a verification task. Behavioral data showed that HMA were slower and more error prone than their LMA peers, and that incorrect solutions were solved more slowly and less accurately than correct ones. Moreover, HMA individuals tended to need more time and commit more errors when having to verify incorrect solutions than correct ones. They also took longer and made more errors than their LMA peers. ERPs time-locked to the presentation of the addends (calculation phase) and to the presentation of the proposed solution (verification phase) were also analyzed. In both phases, a P2 component of larger amplitude was found for HMA individuals than for their LMA peers. Moreover, in the verification phase, LMA individuals showed a larger late positive component (LPC) for incorrect solutions at parietal electrodes than their HMA counterparts. Because the P2 component is considered to be a biomarker of the mobilization of attentional resources towards emotionally negative stimuli, these results suggest that HMA individuals may invest more attentional resources during the arithmetical